ANALISIS PENGARUH PARTIAL SHADING TERHADAP PERFORMANSI MAXIMUM POWER POINT TRACKING PADA ARRAY PHOTOVOLTAIC SUSUNAN SERI-PARALEL MENGGUNAKAN METODE ALGORITMA FIREFLY DAN INCREMENTAL CONDUCTANCE - Rizky Nandasmara Erlangga; Rini Nur Hasanah; Hadi Suyono (Jurnal Mahasiswa TEUB, 2023)
Photovoltaic (PV) systems as a source of renewable electricity generation have experienced rapid development. However, PV systems have several problems, one of which is that the generated electrical power is unbalanced affected by temperature, humidity, irradiation, etc., which makes it difficult to obtain maximum power from PV. In addition, the difference in irradiation levels on each PV module caused by partial shading conditions can cause more than one peak on the PV characteristic curve. This study will compare the performance of the Firefly and Incremental Conductance algorithms in tracking the global peak in the PV characteristic curve. In simulating partial shading conditions, this research uses 6 PV modules connected in series-parallel with 4 test scenarios where each module has a different irradiation value. Simulation testing in this research uses MATLAB-SIMULINK software. Maximum Power Point Tracking (MPPT) simulation results show that from experiments using 4 different test scenarios, the Firefly algorithm obtained an average efficiency of 98.6437%. While the Incremental Conductance algorithm obtained an average efficiency of 78.3448%. So that the percentage of the superiority of the Firefly algorithm over the Incremental Conductance algorithm is 19.9607%. Keyword – Maximum Power Point Tracking (MPPT), partial shading, Photovoltaic (PV), array PV, series-parallel, global peak, local peak, Firefly, Incremental Conductance